2013
DOI: 10.1155/2013/904202
|View full text |Cite
|
Sign up to set email alerts
|

Melissopalynological and Volatile Compounds Analysis of Buckwheat Honey from Different Geographical Origins and Their Role in Botanical Determination

Abstract: Volatile organic compounds (VOCs) have been proposed as one of the main factors for differentiating honeys from different botanical/floral origins. In this work, we investigated the volatile profile of honeys, commercially labeled as buckwheat honeys, from the Alps and its relationship with melissopalynological investigation. The results showed that buckwheat honey samples that contained, to different extents, buckwheat pollen grains on melissopalynological analyses showed similar VOCs profiles, distinguishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
3
22
0
3
Order By: Relevance
“…The research conducted by Panseri et al [55] on buckwheat honey (F. esculentum), from different geographical origins (Russia, Italy and Poland), shows that all volatile compounds were not present in three buckwheat honeys: phenylacetaldehyde was only present in Russian sample, eugenol only in Italian sample, while α-terpinene only in Poland sample and Russian sample.…”
Section: Honey Markers For the Characterization Of Different Unifloramentioning
confidence: 97%
“…The research conducted by Panseri et al [55] on buckwheat honey (F. esculentum), from different geographical origins (Russia, Italy and Poland), shows that all volatile compounds were not present in three buckwheat honeys: phenylacetaldehyde was only present in Russian sample, eugenol only in Italian sample, while α-terpinene only in Poland sample and Russian sample.…”
Section: Honey Markers For the Characterization Of Different Unifloramentioning
confidence: 97%
“…We focused on the effect of 3 factors which were floral source, honeybee species, and postcollection processing. Previous studies reported that floral source was the important factor affecting antibacterial activity in honey (Stanimirova and others ; Panseri and others ). All tested honey samples maintained their antibacterial properties when hydrogen‐peroxide was removed, resulting in the increase of MIC values (antibacterial activity decreased) as shown in Table .…”
Section: Discussionmentioning
confidence: 92%
“…21,78 En mieles florales 4,17,33,34,38 y monoflorales y algunos de los compuestos identificados en éste trabajo han sido relacionados como responsables directos del aroma. 55,57,[79][80][81][82][83] La mayoría de las mieles indistintamente de su origen botánico, presentan más de un componente de los cuales derivan las propiedades y atributos sensoriales.…”
Section: Componentes Volátilesunclassified
“…Algunos de éstos fragmentos son coincidentes con los observados en componentes volátiles de otros tipos de miel. 1,17,31,32,57,80 …”
Section: Componentes Volátilesunclassified
See 1 more Smart Citation